Fresh food access revisited. (January 2016) - Wang, Haoluan; Qiu, Feng
Abstract: This study uses service area-based coverage and Poisson regression methods to assess the neighborhood fresh food environment (supermarkets, local grocery stores, farmers' markets, and community gardens), and investigates the fresh food access in association with different socio-economic groups in Edmonton, Canada. Primary results include that (1) deprived neighborhoods with a larger percentage of unemployed, senior or minority populations have higher access to fresh foods; (2) the rate of children population is negatively associated with fresh food availability; and (3) good access to public transportation is associated with high coverage of fresh food sources, and it plays a special role in improving residents' actual fresh food access. The results have important implications for policy design and public educational campaigns, especially in response to the city's Fresh strategy, which aims to expand the system of local food and urban agriculture and to increase the local food supply and demand. Findings from this article also resonate to the Alberta Project Promoting Active Living and Healthy Eating, which is designed to identify effective ways to create healthy school communities in Alberta. Highlights: Service area-based method considers spatial heterogeneity and solves edge effects. Deprived neighborhoods in general have high access to fresh foods. Adolescent populations face low coverage of fresh foods sources. Areas with convenient access to public transportation have high fresh food access. Support for local grocery stores and community gardens help improve fresh food access.